2015
DOI: 10.1111/jsm.12842
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of Combination Treatment with Injectable Testosterone Undecanoate and Daily Tadalafil for Erectile Dysfunction with Testosterone Deficiency Syndrome

Abstract: Introduction Both testosterone therapy and chronic treatment with phosphodiesterase type 5 inhibitors (PDE5Is) have positive effects on the histology of penile corpora and erectile function. However, few clinical studies have evaluated the efficacy of combination therapy with both testosterone replacement and chronic PDE5Is. Aim This study was designed to evaluate the efficacy and safety of combination treatment with long-act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Increased efficacy of combined T and PDE5i administration compared to PDE5 monotherapy in hypogonadal patients has been shown by several studies (8693). Furthermore, the administration of T undecanoate plus once-daily tadalafil 5 mg is more effective in restoring erectile function than the combination of T undecanoate plus on-demand tadalafil 10–20 mg. Over 30 weeks of treatment, patients treated with T undecanoate plus once-daily tadalafil 5 mg showed higher IIEF5 and AMS scores and, after 6 weeks from treatment discontinuation, a higher percentage of patients had a maintenance of their subjective erectile function improvement (94).…”
Section: Synergic Effects Of T Plus Pde5is In the Treatment Of Erectimentioning
confidence: 99%
“…Increased efficacy of combined T and PDE5i administration compared to PDE5 monotherapy in hypogonadal patients has been shown by several studies (8693). Furthermore, the administration of T undecanoate plus once-daily tadalafil 5 mg is more effective in restoring erectile function than the combination of T undecanoate plus on-demand tadalafil 10–20 mg. Over 30 weeks of treatment, patients treated with T undecanoate plus once-daily tadalafil 5 mg showed higher IIEF5 and AMS scores and, after 6 weeks from treatment discontinuation, a higher percentage of patients had a maintenance of their subjective erectile function improvement (94).…”
Section: Synergic Effects Of T Plus Pde5is In the Treatment Of Erectimentioning
confidence: 99%
“…The basic science literature has confirmed the necessity of androgens to generate adequate intracavernosal pressures and smooth muscle function to obtain an erection [59]. The literature showing the impact of testosterone replacement therapy (TRT) on erectile function is quite heterogenous (Table 1) [6061626364656667686970717273747576777879808182838485868788899091]. A subset analysis of the Olmstead County Cohort published by Gades et al [92] showed that testosterone has a statistically significant positive correlation with erectile function, even when adjusted for age.…”
Section: Hypogonadismmentioning
confidence: 99%